Taxonomic and nomenclatural notes on Jacobaea othonnae (Asteraceae—Senecioneae—Senecioninae) - Sutorý, Karel (Phytotaxa, 2021)
Jacobaea othonnae (M. Bieb.) C.A. Mey., formerly Senecio othonnae M. Bieb., is distributed from the Balkan Peninsula through Anatolia up to the Caucasus and the northern Iranian mountains. On the basis of the variability of its indumentum, its subdivision into three subspecies is proposed. A new subsp. adamsii is described from the eastern part of the distribution range, and a new combination (subsp. anomala) is established for a subspecies narrowly distributed in Greece. Lectotypes for Senecio othonnae, Cacalia anomala and Senecio rariflorus are designated.